Psychoanalysis veterinary: Case of the character Ginger from the book Black Beauty (Sewell, 1877) (Research, Society and Development, 2020)
Zooliterature is a term that refers to texts that present animals in the literary works in different ways. Psychoanalysis is a method used to treat people's mental health, taking as a reference the patients’ statement. Animals can also have imbalances in their mental health. The purpose of this article is to use a character of the equine species from fiction literature to establish a veterinary psychoanalysis, in addition to knowing more about the animal psyche. The character Ginger in the Black Beauty by Anne Sewell, in her original version, told her own story in a dialogue with the protagonist. She suffered a lot in her childhood, first with the separation from her mother, then with physical and psychological violence from human beings. From the character analysis, traumatic hysteria was thought as a diagnosis. Similar to what it would be in a real horse. This knowledge implies ethical issues. Animal psychoanalysis would be limited, as it does not have the speech of animals, although, through its expressions and vocalizations, coupled with the history, it could lead to a better understanding of its intimacy and the answer to the problem, treated with medicaments or management. Also, knowing more about psychoanalysis serves to better understand the human-animal-environment relationship. Finally, zooliterature can be a way of reflecting on these issues.